40Ar-39Ar dating and petrology of monzonite ejecta in tephra from Quaternary Gölcük volcano (Isparta, SW Turkey): tear-related contrasting metasomatic symptoms in extensional mantle-derived magmas - C̦oban, Hakan; Topuz, Gültekin; Schwarz, Winfried H. (Lithos, 2019)
Eruption of (74-26 ka old) pyroclastic (pumice fall) flow deposits of the Quaternary Gölcük volcano, Isparta, SW Turkey, carried a cargo of Western Anatolian’s youngest monzonitic-syenitic ejecta, 40Ar-39Ar hornblende ages range 313+64−268+43 ka, and indicate that a shallow level felsic plutonic complex existed underneath the crater. These ejecta represent some of the youngest plutonic rocks known. The cooling time of this complex was coeval with the earlier main pyroclastic flow deposits (440 - 148 ka) of the multi-cycle eruptive center which also had a long-lived magma chamber. The monzosyenite ejecta contain plagioclase, K-feldspar, clinopyroxene, amphibole, mica, and accessory apatite, titanite and magnetite. In terms of Nb-Y-3Ga and Nb-Y-Ce, the ejecta, with strong shoshonitic affinity, plot in the field of A1 subtype granites, and represent A1-type magma generation in a back-arc extensional setting. Low Sr and high Nd isotopic ratios of monzosyenites exhibit isotopic similarity to enriched mantle-derived Gölcük-Isparta shoshonitic-ultrapotassic magmas. REE patterns show no significant Eu anomaly, but a strong enrichment of the LREE over the HREE. In multi-element diagrams, however, all samples have negative anomalies of Nb_Ta, Zr_Hf, P and Ti and strong enrichments of Ba, Sr, U, and Th. Moreover, variable (Hf/Sm)N and low (Ta/La)N ratios reflect subduction-related metasomatism in their mantle source. Gölcük monzosyenites and shoshonitic-ultrapotassic rocks overlap with mantle-derived A1-type alkali syenites in trace element abundances. This observation suggests that not only subduction-related fluids/melts, but also intraplate sublithospheric metasomatic agents played a crucial role on their mantle source. It is contended that, due to the percolation of both sublithospheric alkali silicate- and subduction-released-melts/fluids, the metasomatized mantle-derived parental magmas may illustrate a chemical paradox, carrying geochemical imprints of genetically distinct types of mantle sources. Such a metasomatic component in continental lithosphere defined in the genesis of Gölcük monzonitic/syenitic magmas can be explained by tearing of the African oceanic slab during Miocene, where slab-derived and intraplate melts/fluids concurrently modified the lithospheric mantle. Metasomatism of wall-rock peridotites occurred prior to the generation of Gölcük magmas during Miocene slab-tearing. Plio-Quaternary Gölcük potassic magmas were possibly derived from partial melting of carbonated mantle metasomes under an extensional tectonic regime.
Gesehen am 29.08.2019
Im Titel sind die Zahlen 40 und 39 hochgestellt